Prevalence of lung metastases in head and neck cancer - A chest radiographic study. - N R Diwakar; G Rajeshwari; B Balaji Rao (Journal of Indian Academy of Oral Medicine and Radiology, 2003)
Lung is by far the most common site for distant metastases from head and neck cancer, accounting for 2.98%` in clinical settings to 37.2%S0 at autopsy. Since, pulmonary metastases produces very few signs and symptoms,(Sun D.X 1992) 6G such metastases influence the treatment and prognosis of the disease process. In life, the detection of pulmonary metastases depends largely on radiographic examination. Routine chest radiographs are the most common way of detecting metastatic disease (Crow 1981) 53. This study attempts to find the clinical prevalence of lung metastases from head and neck cancer in general and oral cavity in particular, using chest radiographs and review the selected related literature.